1982
DOI: 10.1139/y82-164
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid formation in rats and cats during treatment with timolol

Abstract: The influence of timolol upon cerebrospinal fluid formation rate has been examined in rats by the measurement of 22Na+ entry into this fluid after 10, 100, or 1000 micrograms x kg-1 i.v. and in cats by the dye-dilution measurement of new fluid formation after 30, or 3000 microgram x kg-1 i.v., or 250 micrograms x mL-1 in ventricular perfusate. In rats no change from control rates occurred. In the cats there appeared to be no effect of intraventricular timolol; however, a significant decrease of approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Timolol maléate is another example of a compound that lowers blood pressure (20), slows aqueous humor formation (21) and also slows cerebrospinal fluid formation (22). Renin inhibitors have been shown to reduce systemic arterial blood pressure (7), and the present study reported on the ability of the renin inhibitor, enalkiren, to cause a reduction of IOP in animals.…”
Section: Resultsmentioning
confidence: 69%
“…Timolol maléate is another example of a compound that lowers blood pressure (20), slows aqueous humor formation (21) and also slows cerebrospinal fluid formation (22). Renin inhibitors have been shown to reduce systemic arterial blood pressure (7), and the present study reported on the ability of the renin inhibitor, enalkiren, to cause a reduction of IOP in animals.…”
Section: Resultsmentioning
confidence: 69%